(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
In a globalized world, where the generation and dissemination of knowledge constitute fundamental pillars for the development of societies, Revista FACE emerges as a space for academic openness that transcends borders. Our mission is to provide a scientific dissemination platform that enables the exchange of ideas and the strengthening of research in economic and administrative sciences at an international level. In this regard, it is an honor to present in this edition a selection of articles that reflect the diversity of academic thought in different regions, addressing challenges and opportunities through innovative approaches and rigorous methodologies. One of the most outstanding works from Rey Juan Carlos University in Spain is "Improvements and Adjustments to GDP: How to Measure a More Realistic Well-being?", a study conducted by a group of Spanish researchers that reconsiders the effectiveness of Gross Domestic Product (GDP) as the main indicator of economic growth and social well-being. This interdisciplinary study in Political Economy, Macroeconomics, and Economic Sociology highlights the inherent biases of traditional national accounting models, especially in service-based and digitalized economies. The research provides a comprehensive perspective on more accurate and realistic measurement tools that could offer valuable inputs for macroeconomic management and the formulation of more inclusive and sustainable public policies. From Asia, Central China Normal University, through a group of Chinese researchers, offers an in-depth analysis of "The Investment Environment in Argentina Using the Analytic Hierarchy Process (AHP)". This study is particularly relevant in the context of increasing economic cooperation between Argentina and China, allowing investors to comprehensively evaluate the environment before making strategic decisions. Using AHP, the article examines five key aspects: political, economic, social, infrastructural, and regulatory, establishing a reference framework for improving decision-making in emerging markets. The applicability of this methodology to different economic contexts makes this study a substantial contribution to both the academic and business communities. On the other hand, from Universidad Laica Eloy Alfaro de Manabí in Ecuador, the article "Experiential Marketing and Its Influence on the Purchasing Behavior of Movistar Customers in the Province of Manabí" is presented. Through a non-experimental quantitative approach and the application of surveys using a Likert scale questionnaire, this study demonstrates the strong correlation between experiential marketing strategies and consumer purchasing decisions. The findings reveal that sensory, emotional, and relational experiences significantly impact customer loyalty, validating the effectiveness of experiential marketing in emerging markets and its applicability in business strategies. Also noteworthy is the study from Mexico, "The Impact of Emotional Neuromarketing on Social Media as an Influence on the Purchasing Decisions of University Students in Tabasco." In a world dominated by digital interactions, this article explores how visual, auditory, and kinesthetic stimuli on social media can influence young university students’ purchasing decisions. Based on surveys conducted among students in Villahermosa, Tabasco, the study shows that emotional neuromarketing not only strengthens brand positioning but also fosters a deeper understanding of consumer behavior in digital environments, providing key insights for designing more effective business strategies. It is also important to highlight other studies presented by authors representing Mexican institutions such as Universidad de Monterrey, Universidad de Colima, Universidad Autónoma de Puebla, Universidad Juárez Autónoma de Tabasco, and Universidad Autónoma de Ciudad Juárez. These studies reflect the richness and diversity of academic thought on a global scale, as well as the relevance of Revista FACE as a dissemination channel for high-impact research. Our commitment remains to provide a space for discussion and analysis that contributes to the development of knowledge in the field of economic and administrative sciences. We thank the authors for their valuable contributions and our readers for being part of this global academic community.